Association between adhesive capsulitis and depression: A five-year retrospective cohort study including 58, 516 adults from Germany. (November 2022) - Jacob, Louis; Koyanagi, Ai; Oh, Hans; Smith, Lee; Konrad, Marcel; Shin, Jae Il; Haro, Josep Maria; Kostev, Karel
Abstract: Background: Little is known on the longitudinal relationship between adhesive capsulitis and depression. Therefore, the aim of this study was to investigate the association between adhesive capsulitis and the five-year cumulative incidence of depression in adults from Germany. Methods: The present retrospective cohort study included all adults aged ≥18 years with a first diagnosis of adhesive capsulitis in one of 1198 general practices in Germany between January 2010 and December 2018 (index date). Patients with adhesive capsulitis were matched to those without adhesive capsulitis using a propensity score based on age, sex, index year, average number of visits per year, and diagnoses documented prior to or at the index date (i.e., thyroid gland disorders, diabetes mellitus, coronary heart disease, cerebrovascular diseases, and Parkinson's disease and secondary parkinsonism). In individuals without adhesive capsulitis, the index date was a randomly selected visit date. Results: This study included 29, 258 patients with and 29, 258 patients without adhesive capsulitis (mean [SD] age 55.9 [15.6] years; 53.2% men). Within five years of the index date, there were 17.5% of patients with adhesive capsulitis and 8.7% of those without adhesive capsulitis diagnosed with incident depression (log-rank p-value<0.001). This result was corroborated in the Cox regression analysis, as there was a positive and significant association between adhesive capsulitis and the cumulative incidence of depression (HR = 1.86, 95% CI: 1.78–1.95). Conclusion: In this study, adhesive capsulitis was associated with an increased cumulative incidence of depression. Further research is warranted to better understand the mediating factors involved in this relationship. Highlights: This study included 58, 516 patients with and without adhesive capsulitis. The incidence of depression was 17.5% in the group with adhesive capsulitis. The incidence of depression was 8.7% in the group without adhesive capsulitis. Adhesive capsulitis was significantly associated with incident depression (HR = 1.86).